2014
DOI: 10.1039/c3cc47481j
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-catalyzed carbene transfer to alkynes via 2-furylcarbenes generated from enynones

Abstract: A rhodium-catalyzed carbene transfer to alkynes is reported. Easily available enynones served as the carbene source replacing diazocompounds. The overall process involved a cyclization-cyclopropenation-ring enlargement sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Recently, Rh(II)-catalyzed cyclopropenation of 2-furylcarbenes from enynones was reported (Scheme 30). 47 As expected, the cyclopropenes 83 can only be isolated at low temperature (0 C) and with a short reaction time (0.5-2 hr). When the reaction was conducted at a higher temperature ( form a second vinyl carbene, followed by an S E Ar reaction to give rise to different furan derivatives.…”
Section: Reactions Via Carbene Intermediatessupporting
confidence: 65%
See 1 more Smart Citation
“…Recently, Rh(II)-catalyzed cyclopropenation of 2-furylcarbenes from enynones was reported (Scheme 30). 47 As expected, the cyclopropenes 83 can only be isolated at low temperature (0 C) and with a short reaction time (0.5-2 hr). When the reaction was conducted at a higher temperature ( form a second vinyl carbene, followed by an S E Ar reaction to give rise to different furan derivatives.…”
Section: Reactions Via Carbene Intermediatessupporting
confidence: 65%
“…(2) no slow addition of the carbene precursor required (the dimerization reaction of enynals and enynones is typically much slower). The 2-furanyl carbene generated in 5-exo-dig cyclization demonstrated various applications in carbene transfer reactions, including oxidation, 46 cyclopropanation, [31][32][33] cyclopropenation, 47 C-H insertion, 48 X-H insertion, 33,49 aziridination, 50 cross-coupling, 51,52 and so on (Scheme 27).…”
Section: Reactions Via Carbene Intermediatesmentioning
confidence: 99%
“…The dienone undergoes pericyclic ring closure to afford the final product. A M a n u s c r i p t [1052]. The proposed mechanism involves the formation of a furylcarbenerhodium complex (e.g.…”
Section: Scheme 78 Group 9 Nhc Complexesmentioning
confidence: 99%
“…As an alternative to diazo compounds as carbene precursor, Vicente et al reported the rhodiumcatalyzed cyclopropenation of alkynes using conjugated enynones as diazo surrogates. 23 Interestingly, an implementation of this strategy with the unprecedented use of zinc catalysts in cyclopropenations was also reported. 24 Indeed, inexpensive ZnCl 2 proved to have superior activity in these reactions with respect to widely used dirhodium carboxylates, including reactions with internal alkynes (Scheme 8).…”
Section: Short Review Syn Thesismentioning
confidence: 99%